HUBUNGAN PENGETAHUAN IBU TENTANG VITAMIN A DENGAN PEMBERIAN VITAMIN A PADA BALITA DI DESA KUANTAN SAKO TAHUN 2016 - Rinda Fithriyana (Universitas Pahlawan Tuanku Tambusai, 2018)
As many as 190 million children younger than 5 years have vitamin A deficiency. WHO estimates that there are 250 million preschool children who suffer from blindness and some of these children then die within 12 months due to vitamin A deficiency. Vitamin A is one of the important nutrients that dissolve in fat and stored in the liver, can not be made by the body, so it must be met from the outside (essensial), serves for vision, growth and increase endurance against disease. The purpose of this study to determine the relationship of knowledge of mother about vitamin A with vitamin A in infants in the area of the village of Kuantan Sako in 2016. The research design used is cross sectional. The sampling technique used is simple random sampling with the number of samples of 81 people. Result of research got that mother knowledge about vitamin A mostly low that is as much 56 responden (69,1%). There is a correlation between mother's knowledge about vitamin A with vitamin A supplementation in toddler in Kuantan Sako Village Area 2016 with P value = 0,000 (P â‰¤ 0,05) It is expected for health officer especially in Working Area of Desa Kuantan Sako in order to increase counseling about knowledge giving Vitamin A in toddlers and is expected for mothers to be able to find information about the needs of children under five years of growth so that the needs of vitamin A can be met